PERBANDINGAN HASIL PEMERIKSAAN TINJA METODE SEDIMEN DENGAN METODE FLOATING PADA INFEKSI KECACINGAN - NELI ADELIA RESMALITA; NURFADLY NURFADLY (LP2MTBM MAKARIOZ, 2023)
The use of the examination method has high sensitivity and specificity for Soil Transmitted Helminth (STH), which is very important for early detection of the infection. Research has been carried out on the comparison of the results of the examination of the Sediment method with the Floating method on helminth infections. To compare the results of the floating method of stool examination in helminth infections. The diagnostic test with the research sample is the sample taken from the students of grade 3.4.5. and 6 who live in the Putri Aisyıyah Orphanage in Medan City. The examination was carried out at the Parasite Laboratory, Faculty of Medicine, University of Muhammadiyah North Sumatra. The examination was carried out using the Sediment, Floating, and Direct Method (gold standard) methods. There were 4 positive samples of Soil Transmitted Helminth (STH) from 30 samples examined. The method that mostly detects Soil Transmitted Helminth (STH) is the Sediment method and the direct method (gold standard) with 4 samples. Sediment method has sensitivity (100%) and specificity (100%), Floating method has sensitivity (50%) and specificity (100%). The results showed that the number of samples infected with Soil Transmitted Helminth (STH) was more commonly found using the Sediment method. The Sediment method has a higher sensitivity (100%) and specificity (100%) than the Floating method. The results of the tests that have been carried out on the Sediment and Floating methods, concluded that the best method for detecting Soil Transmitted Helminths (STH) can be used as an alternative to the direct method (gold standard) is the Sediment method.